2022
DOI: 10.1155/2022/4066385
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Application of the Classical Theory of Traditional Chinese Medicine in Diabetic Nephropathy

Abstract: Objective. To explore the clinical application of the classical theory of traditional Chinese medicine (TCM) in diabetic nephropathy (DN). Methods. A total of 100 patients with DN treated in our hospital from May 2019 to June 2021 were included. The patients were randomly assigned to the control group and the study group. The control group received routine treatment, and the study group was treated with the classical theory of TCM. The efficacy, TCM syndrome score, urine proteinuria (UTP), urine albumin-creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…TCM is favored by numerous T2DM patients [ 25 ] and DN patients [ 26 ] by virtue of attributes such as a multi-target approach, low toxicity, and few side effects. Owing to its spleen-strengthening and yang-nourishing abilities, Zhenwu decoction has been a mainstay of Chinese clinical practice for thousands of years.…”
Section: Discussionmentioning
confidence: 99%
“…TCM is favored by numerous T2DM patients [ 25 ] and DN patients [ 26 ] by virtue of attributes such as a multi-target approach, low toxicity, and few side effects. Owing to its spleen-strengthening and yang-nourishing abilities, Zhenwu decoction has been a mainstay of Chinese clinical practice for thousands of years.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous randomized controlled trial (RCT) research has proved that JCYSTLF has a significant improvement in urinary protein and renal function in DN patients, which provides evidence for JCYSTLF to improve renal injury in diabetes [ 6 ]. Moreover, our previous studies have showed that JCYSTLF is related to its anti-aging effect in patients with type 2 diabetes [ [7] , [8] , [9] ]. However, little is known about the anti-senescence mechanism of JCYSTLF.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%